The Ethical Crisis in the State Honduran since the coup State of 2009 - Bourdet Carrasco, Keidy Gabriela (Teoría y Praxis, 2022)
It is intended to analyse the relationship between ethics and politics, in the same way that it has deteriorated since it was established since ancient times by the philosophers Plato and Aristotle. Ethics are essential to politics, both are oriented towards good, but those who are engaged in politics are the main example of corruption in Honduras, as they have lost sight of the search for the common good and have focused only on gaining power and enriching themselves. Since the coup d’état of the 2009 in Honduras, it seems that the crisis between ethics and politics has deepened further.